The Effects of Boric Acid on The Water Solubility of Glass Ionomer Cements - Cukurluoz Bayındır, Banu; Bağ, İrem (UI Scholars Hub, 2023)
Changing the water solubility property of glass ionomer cement (GIC), which is frequently used in pediatric dentistry, is the starting point of this study. Objective: To evaluate the effects of boric acid on the water solubility (WS) of GIC. Methods: The samples were prepared as n=12 in each of four groups: GIC-Conventional glass ionomer cement; BGIC with 1:3 boric acid added to conventional GIC powder; RMGIC-resin-modified glass ionomer cement; BRMGIC with 1:3 boric acid added to RMGIC powder. Weight changes were compared 1, 3 and 24 h after keeping in distilled water. One sample in each group was measured by SEM-EDX analysis. The data were analyzed using a one-way analysis of variance, Dunnett’s T3 in multiple comparison tests, and generalized linear models. Results: In all groups, water solubility increased. There was a significant difference between the mean values of the WS-1h, WS-3h, and WS-24h variables in each group and between the GIC, BGIC, RMGIC, and BRMGIC groups in the mean values of the WS-1h, WS-3h, and WS-24h variables. The SEM-EDX analysis revealed 14.19–18.47%; 0.80–1.00%; 8.69–14.91%; 0.09–13.10% boron minerals in GIC, BGIC, RMGIC, and BRMGIC, respectively. 8: The addition of boric acid led to an increase in water solubility. The effects of boric acid on the GIC samples emphasized its potential role in altering the cement’s physicochemical properties. Therefore, it is important to consider carefully when using boric acid as a supplement in GIC formulations for dental applications.